2007
DOI: 10.1152/japplphysiol.00912.2006
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the functional role of arterial pathways to the buttock circulation during treadmill walking in patients with claudication

Abstract: The aim of the study was to estimate the functional contribution of the arterial inflow pathways to the pelvic circulation during walking in patients with stage 2 lower extremity arterial disease. Transcutaneous oxygen pressure (Ptc(O(2))) changes during exercise can be used to estimate the severity of regional blood flow impairment while walking. Seventy patients with stable lower limb claudication were studied using a multivariate linear regression model. The relationship between exercise-induced buttock Ptc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…The main symptom is the lower back, hip, buttock, or thigh claudication defining the proximal claudication, a fatigue, discomfort, or pain occurring in specific muscle groups alimenting by IIA during effort due to exercise-induced ischemia and which is relieved with rest ( 2 , 6 ). However, the presentation of proximal claudication is often atypical and may mimic other non-vascular diseases that may induce misleading diagnoses ( 5 , 9 ) (Figure 1 ).…”
Section: Symptoms and Functional Impairmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The main symptom is the lower back, hip, buttock, or thigh claudication defining the proximal claudication, a fatigue, discomfort, or pain occurring in specific muscle groups alimenting by IIA during effort due to exercise-induced ischemia and which is relieved with rest ( 2 , 6 ). However, the presentation of proximal claudication is often atypical and may mimic other non-vascular diseases that may induce misleading diagnoses ( 5 , 9 ) (Figure 1 ).…”
Section: Symptoms and Functional Impairmentmentioning
confidence: 99%
“…Claudication traditionally stops within 10 min after the end of walking ( 22 , 23 ). The maximal walking distance often impairs either with the increase of the arterial stenosis or the deterioration of the functionality of the collateral network, which both diminish blood flow delivery to muscles irrigated by the IIA ( 6 ). The maximal walking distance can be evaluated by different methods: medical interview, questionnaires ( 24 ), standardized treadmill evaluation which is recommended ( 11 ), 6-min test when patients are unable to walk on a treadmill ( 11 ), and recently GPS technology ( 25 ).…”
Section: Strategies and Evidencesmentioning
confidence: 99%
See 1 more Smart Citation
“…We assume that this is not the explanation since no worsening was observed on the right buttock. The role of circumflex iliac arteries is clearly not dominant in models of the pelvic circulation [8]. Nevertheless, when dominant pathways (lumbar or ipsilateral and contra hypogastric arteries) are occluded, such arteries may become essential to cover muscle blood flow requirements at exercise.…”
Section: Discussionmentioning
confidence: 99%
“…26 The pelvic circulation is a complex network and many pathways may participate in the blood flow supply in the case of hypogastric chronic occlusion. 6 It is likely that penile pressure is maintained within normal ranges if one hypogastric artery is chronically occluded and that pressure falls only when lesions are present bilaterally, whereas unilateral acute occlusion might be detected better. This is probably why previous studies have shown a significant difference in penile to brachial pressure index between normal arteriograms and bilateral, but not unilateral, lesions.…”
Section: Discussionmentioning
confidence: 99%